Chapter Determination of natural radioactivity levels of sludges collected from wastewater treatment plants of Antalya/Türkiye - OZMEN, Suleyman Fatih (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
226Ra (10.8), 232Th (13.4) and 40K (135.7) and 137Cs (3.2) concentration levels (Bq kg-1) of the wastewater treatment plant sludges in Antalya were assessed and were found to be consistent with the literature. The absorbed gamma dose rate (D: 3.1-17.5 nGyh-1), radium equivalent activity (Raeq: 6.4-37.7 Bq kg-1), annual equivalent dose (AED: 3.8-21.4 µSv h-1), internal (Hin<1.0) and external (Hex<1.0) hazard indices were in the permissible limits published by IAEA. It was observed that the use of wastewater treatment sludge in agricultural areas would not create any risk in radiological terms.